2020
DOI: 10.21203/rs.2.23305/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of immune-related biomarkers associated with tumorigenesis and prognosis in cutaneous melanoma patients

Abstract: Background:Skin cutaneous melanoma (SKCM) is one of the most malignant and aggressive cancers, causing about 72% of deaths in skin carcinoma. Although extensive study has explored the mechanism of recurrence and metastasis, the tumorigenesis of cutaneous melanoma remains unclear. Exploring the tumorigenesis mechanism may help identify prognostic biomarkers that could serve to guide cancer therapy. Methods:Integrative bioinformatics analyses, including GEO database, TCGA database, DAVID, STRING, Metascape, GEPI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…On this basis, we found that the immune cell components of patients in these two groups were also different, mainly in naïve B cells, memory B cells, plasma cells, CD8 + T cells, naive CD4 + T cells, resting CD4 + memory T cells, activated CD4 + memory T cells, and regulatory T cells, in line with previous findings [ 28 ]. For example, CD8 + T cells play an important role in the tumor microenvironment, which inhibits the proliferation and metastasis of tumor cells [ 29 ]. Our results indicate that CD8 + T cells were highly expressed in low immune risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, we found that the immune cell components of patients in these two groups were also different, mainly in naïve B cells, memory B cells, plasma cells, CD8 + T cells, naive CD4 + T cells, resting CD4 + memory T cells, activated CD4 + memory T cells, and regulatory T cells, in line with previous findings [ 28 ]. For example, CD8 + T cells play an important role in the tumor microenvironment, which inhibits the proliferation and metastasis of tumor cells [ 29 ]. Our results indicate that CD8 + T cells were highly expressed in low immune risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that CXCL12 and CCL27 played an important role in CM metastasis, and were mainly involved in SKMC metastasis through the CXCR4-CXCR7-CXCL12 axis and CCL27-CCR10 axis [ 39 , 40 ]. CXCL9 and CXCL13 have been confirmed to be overexpressed in both primary SKCM and metastatic CM [ 41 , 42 ]. As ligands of CCR7, CCL19 and CCL21 play an important role in the migration of immune cells (T cells and dendritic cells), and deviation in the regulation of the CCR7-CCL19/CCL21 axis may lead to and cause the occurrence and metastasis of tumors [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then gene set variation analysis (GSVA) package is applied to calculate the degree of immune cell in ltration based on gene expression pro les [19]. These ways have been employed to estimate the relative abundance of immune cells from various cancers such as hepatocellular carcinoma [20] and cutaneous melanoma [21].…”
Section: Introductionmentioning
confidence: 99%